Transcranial Approach for Venous Embolization of Dural Arteriovenous Fistula - de Macêdo, Lívio Pereira; Silva, Francisco Ranilson Alves; Junior, Marcos Alcino Soares Siqueira Marques; Rolim, Daniel Duarte; Queiroz, Sildomar; Cysneiros, Renata Raizza Monterazzo; da Silva, Ubiratan Alves Viturino; Silva, José Laércio Júnior; Andrade, Gustavo; Almeida, Nivaldo S.; Azevedo-Filho, Hildo Rocha Cirne (Arquivos Brasileiros de Neurocirurgia: Brazilian Neurosurgery, 2025)
Transvenous embolization emerges as a viable intervention for addressing intracranial dural arteriovenous fistulas (DAVF). Accessibility to the fistulous site via the internal jugular vein (IJV) may be impeded by associated dural sinus apoplexy or thrombosis, prompting the development of a transcranial approach for venous embolization in such scenarios. The presented case details the utilization of a transcranial approach for venous embolization of DAVF. This method allows unobstructed entry to DAVFs situated on superficial dural sinuses that lie beyond the reach of the IJVs. The efficacy of this approach parallels that of the conventional retrograde venous methodology. The precise location and appropriate extent of the craniectomy play pivotal roles in ensuring the success of this technique.
Keywords: Transcranial approach; venous embolization; dural arteriovenous fistula